ANALISIS TINJAUAN AL-QUR’AN TERHADAP MODEL PEMBELAJARAN PENDEKATAN PSIKOLOGI HUMANISTIK CARL ROGERS - Muchamad Sihabul Millah; M. Rijal Mukafiy (PT. Hasba Edukasi Mandiri, 2026)
Carl Rogers' humanistic psychological approach has been highly influential and beneficial to the learning system. His ideas also tend to form the basis for the development of this approach.Student-Centered Learning(SCL), which is now increasingly used by various educational institutions, is replacing the classroom learning model.Teacher-Centered Learning(TCL). This study aims to examine the advantages of the SCL-based learning model through an analysis of Carl Rogers' humanistic psychology approach and the values contained in the Qur'an, both of which have similarities in their basic principles. There are two problems in this study, namely: (1) How is Carl Rogers' humanistic psychology approach learning model?, (2) How is the analysis of the Qur'an's review of Carl Rogers' humanistic psychology approach learning model? This research uses a qualitative approach with a literature study type of research.(library research). The method used is This research uses a descriptive analysis method that will be used to examine the verses of the Quran related to the Carl Rogers learning approach model. The data collection technique in this research is carried out through documentation studies or library research. The research results show that (1) Carl Rogers' learning model places students as the center of learning, with an emphasis on subjective experience, self-actualization, and authentic relationships in an empathetic and supportive learning environment. (2) The Qur'an does not contradict this approach, but rather enriches the direction of education towards spiritual, moral, and intellectual perfection within the framework of devotion to Allah SWT.